Genetic Divergence for the Amphibian Pleurodeles waltl in Southwest Portugal: Dispersal Barriers Shaping Geographic Patterns - Van Vliet, Mirjam (2018)
Dispersal and vicariance are the principal mechanisms responsible for the formation of biogeographic patterns, driven or maintained by the role of past and current barriers to dispersal. Southwest Portugal harbors a rich endemic fauna and flora where strongly differentiated taxa can be observed, suggesting ancient isolating mechanisms acted in this region. In this study, we used information from two partial mitochondrial sequences, combined with information from microsatellite loci and amplification success, to investigate biogeographic patterns of genetic divergence in populations of Pleurodeles waltl in Portugal. Our results demonstrate genetic differentiation at different time frames creating distinct populations in southwest Portugal, which might have arisen following isolation by a large river estuary and mountainous barriers. Habitat destruction associated with agricultural intensification raises conservation concerns over the unique biodiversity in this region.